2020
DOI: 10.1101/2020.05.04.077792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrograde labeling illuminates distinct topographical organization of D1 and D2 receptor-positive neurons in the prefrontal cortex of mice

Abstract: The cortex plays an important role in regulating motivation and cognition, and does so by regulating multiple subcortical brain circuits. Glutamatergic pyramidal neurons in the prefrontal cortex (PFC) are topographically organized in different subregions such as the prelimbic, infralimbic and orbitofrontal, and project to topographically-organized subcortical target regions.Dopamine D1 and D2 receptors are expressed on glutamatergic pyramidal neurons in the PFC.However, it is unclear whether D1 and D2 receptor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Our studies have recently identified a possible cortico-striatal-midbrain circuit mechanism for cortical dopamine control of striatal dopamine function and behaviors (Green et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Our studies have recently identified a possible cortico-striatal-midbrain circuit mechanism for cortical dopamine control of striatal dopamine function and behaviors (Green et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Activation of D2Rs on interneurons has been shown to decrease IPSCs on pyramidal neurons (Seamans et al, 2001). D2Rs are also expressed on pyramidal neurons and their activation appears to play an excitatory role but the effect appears less robust than D1R activation (Green et al, 2020;Lançon et al, 2021). DA receptor subtype 3 (D3Rs) are also present in L2/ 3 ACC and although less is known about their direct effect on neuron excitability, they appear to play a role in gating the release of DA, NE, and ACh (Lacroix et al, 2003).…”
Section: Dysregulated Acc Major Contributor To Pathological Pain Proc...mentioning
confidence: 99%